2019
DOI: 10.1002/pbc.27913
|View full text |Cite
|
Sign up to set email alerts
|

Use of complement monoclonal antibody eculizumab in Shiga toxin producing Escherichia coli associated hemolytic uremic syndrome: A review of current evidence

Abstract: Complement activation plays an important role in the pathogenesis of atypical hemolytic uremic syndrome. Eculizumab is a monoclonal antibody that blocks complement activity and has been approved for use in the treatment of atypical hemolytic uremic syndrome (HUS). Less well appreciated is the role of complement in Shiga toxin-induced HUS (Shiga toxin producing Escherichia coli[STEC]-HUS). To a limited extent, eculizumab has been used off label in patients with severe STEC-HUS with neurological involvement. Thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
(24 reference statements)
0
13
0
3
Order By: Relevance
“…Based on the interaction of Stx2 with the complement system [ 251 ], the C5-complement inhibiting monoclonal antibody Eculizumab was therapeutically employed as rescue therapy for EHEC–HUS patients, which had seizures or were in a stupor or coma [ 490 ]. In a number of studies, Eculizumab showed positive clinical improvement after treatment in severe EHEC-HUS with progressive neurological improvement that often lead to serious long-term disabilities [ 491 ]. In particular, the early use of Eculizumab appeared to improve neurological outcome suggesting that prophylactic antibody therapy before the development of neurological symptoms could be advantageous [ 490 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the interaction of Stx2 with the complement system [ 251 ], the C5-complement inhibiting monoclonal antibody Eculizumab was therapeutically employed as rescue therapy for EHEC–HUS patients, which had seizures or were in a stupor or coma [ 490 ]. In a number of studies, Eculizumab showed positive clinical improvement after treatment in severe EHEC-HUS with progressive neurological improvement that often lead to serious long-term disabilities [ 491 ]. In particular, the early use of Eculizumab appeared to improve neurological outcome suggesting that prophylactic antibody therapy before the development of neurological symptoms could be advantageous [ 490 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, case series and case control studies yielding equivocal results [ 191 ], and two randomized controlled trials completed in 2012 (NCT01410916) and 2018 (NCT02205541) without any publication have cast doubts over the efficacy of complement inhibition in this indication.…”
Section: Managementmentioning
confidence: 99%
“…However, it has been used in some cases of severe STEC-HUS with some efficacy. 15,16 In this case, we had planned to start eculizumab treatment due to brain involvement secondary to severe STEC-HUS.…”
Section: Discussionmentioning
confidence: 99%